Comparative efficacy of 2% minoxidil alone against combination of 2% minoxidil and low-level laser therapy in female pattern hair loss–A randomized controlled trial in Chinese females - Xianhong Yang; Rui Qiao; Wei Cheng; Xuemei Lan; Yufen Li; Yiqun Jiang (Photodiagnosis and Photodynamic Therapy)
Objectives: To investigate the effectiveness and safety of combination of 655 nm low level laser helmet device with topical 2 % minoxidil solution at FPHL in Chinese population. Materials and methods: Randomized, parallel, controlled, single-blind clinical trial was conducted. FPHL subjects were randomly allocated into 2 % minoxidil group and combination group. The 2 % minoxidil group received 1 ml topical 2 % minoxidil solution twice daily for 24 weeks. The combination group received 1 ml topical 2 % minoxidil solution twice daily together with 20 min 655 nm low-level laser helmet once every other day for 24 weeks. Hair parameters in two scalp areas including midscalp and vertex were evaluated at baseline, 12th week and 24th week. Results: In midscalp area, the combination group showed a lower increase in intermediate hair percentage than 2 % minoxidil group, which was statistically significant. Besides, the combination group had statistically significant increase than 2 % minoxidil group in mean hair diameter. Reported relative adverse events included slightly hair loss (27.8 %), desquamation (19.0 %), pruritus (15.2 %), seborrhea (2.5 %) and hypertrichosis (2.5 %). Conclusion: In our trial, LLLT was demonstrated as a useful supplementary treatment for FPHL and the combination with 2 % minoxidil accomplished better improvement in intermediate hair enlargement and hair diameter of midscalp for FPHL